The neural correlates of the body-object interaction effect in semantic processing - Hargreaves, Ian S. (Frontiers Media S.A., 2012)
The semantic richness dimension referred to as body-object interaction (BOI) measures perceptions of the ease with which people can physically interact with words' referents. Previous studies have shown facilitated lexical and semantic processing for words rated high in BOI, e.g., belt, than for words rated low in BOI, e.g., sun. These BOI effects have been taken as evidence that embodied information is relevant to word recognition (Siakaluk et al., 2008a). However, to date there is no evidence linking BOI manipulations to differences in the utilization of perceptual or sensorimotor areas of the brain. The current study used event-related functional magnetic resonance imaging (fMRI) to examine the neural correlates of BOI in a semantic categorization task (SCT). Sixteen healthy adults participated. Results showed that high BOI words were associated with activation in the left inferior parietal lobule (supramarginal gyrus, BA 40), a sensory association area involved in kinesthetic memory. These results provide evidence that the BOI dimension captures the relative availability of sensorimotor information, and that this contributes to semantic processing.